Summit camp during the construction of the White Pass & Yukon Railroad, White Pass, Alaska, February 2, 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows horse drawn sleds hauling lumber. Caption on image: "Summit camp on the White Pass and Yukon Route Feb 2nd '99" Original image in Hegg Album 2, page 9.